2009
DOI: 10.3177/jnsv.55.215
|View full text |Cite
|
Sign up to set email alerts
|

1α,25 Dihydroxyvitamin D3: Therapeutic and Preventive Effects against Oxidative Stress, Hepatic, Pancreatic and Renal Injury in Alloxan-Induced Diabetes in Rats

Abstract: Summary Diabetes mellitus is a major endocrine disorder and a growing health problem in most countries which can be ameliorated by numerous bio-molecules such as 1 ␣ ,25 dihydroxyvitamin D3 [1 ␣ ,25(OH)2VD3]. With this in mind, the current study investigated the therapeutic and preventive effects of 1 ␣ ,25(OH)2VD3 on diabetes and its side effects: toxicity in liver, pancreas and kidneys. Our results show that administration of 1 ␣ ,25(OH)2VD3 in diabetic rats increased the plasmatic insulin level, favored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 37 publications
6
71
0
3
Order By: Relevance
“…Several studies demonstrated that vitamin D may reduce lipid peroxidation (21,22). Kuzmenko and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that vitamin D may reduce lipid peroxidation (21,22). Kuzmenko and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is a well-documented suppressor of oxidative stress [13][14][15]. Vitamin D-dependent activation (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), calcium (Ca), and phosphorus (P) levels were measured using an autoanalyzer (No.…”
mentioning
confidence: 99%
“…In COPD, the expression and activity of Nrf2 has been shown to be decreased despite high levels of oxidative stress in the lungs (Goven et al, 2008;Suzuki et al, 2008). Several studies suggest that vitamin D or vitamin D analog therapy may suppress oxidative stress in several disease models (Noyan et al, 2005;Hamden et al, 2009;Husain et al, 2009;Fedirko et al, 2010;Tanaka et al, 2011), and this could be related to the effect of vitamin D on Nrf2 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%